Associations Between Air Pollution and Peak Expiratory Flow Among Patients with Persistent Asthma - Qian, Zhengmin (2009)
Responses of patients with persistent asthma to ambient air pollution may be different from those of general populations. For example, asthma medications may modify the effects of ambient air pollutants on peak expiratory flow (PEF). Few studies examined the association between air pollution and PEF in patients with persistent asthma on well-defined medication regimens using asthma clinical trial data. Airway obstruction effects of ambient air pollutants, using 14,919 person-days of daily self-measured peak expiratory flow (PEF), were assessed from 154 patients with persistent asthma during the 16 wk of active treatment in the Salmeterol Off Corticosteroids Study trial. The three therapies were an inhaled corticosteroid, an inhaled long-acting β-agonist, and placebo. The participants were nonsmokers aged 12 through 63 yr, recruited from 6 university-based ambulatory care centers from February 1997 to January 1999. Air pollution data were derived from the U.S. Environmental Protection Agency Aerometric Information Retrieval System. An increase of 10 ppb of ambient daily mean concentrations of NO(2) was associated with a decrease in PEF of 1.53 L/min (95% confidence interval [CI] −2.93 to −0.14) in models adjusted for age, gender, race/ethnicity, asthma clinical center, season, week, daily average temperature, and daily average relative humidity. The strongest association between NO(2) and PEF was observed among the patients treated with salmeterol. Negative associations were also found between PEF and SO(2) and between PEF and PM(10), respectively. The results show that the two medication regimens protected against the effects of PM(10). However, salmeterol increased the sensitivity to NO(2) and triamcinalone enhanced the sensitivity to SO(2).